Farmers' Understanding of Rice Farming Commercialization in South Bengkulu Regency - Mulyasari, Gita; Oktami, Evon Tri; Sukiyono, Ketut (AGRITROPICA : Journal of Agricultural Sciences, 2025)
This study analyzes farmers’ understanding of farm commercialization and identifies the factors influencing it in South Bengkulu Regency, a leading rice-producing area in Bengkulu Province, Indonesia. A total of 88 rice farmers were surveyed using structured questionnaires, and data were analyzed through descriptive statistics and multiple linear regression. The findings reveal that farmers’ understanding of commercialization falls within the understanding category (average score: 3.51). Among the indicators, price understanding achieved the highest score (3.93), followed by market orientation (3.70). Risk (3.31) and institutional aspects (3.08) remained relatively low. Regression analysis indicates that formal education, farming experience, access to extension services, rice field type (irrigated vs. rainfed), and land size significantly influence farmers’ understanding (R² = 0.624). These results indicate that both internal factors (education and experience) and external factors (extension, irrigation systems, and farm size) jointly determine farmers’ capacity to understand and apply commercialization concepts. Strengthening non-formal education, enhancing extension services, and supporting farmer institutions are essential to improve farmers’ market orientation. Strengthened understanding of commercialization is expected to increase household welfare and contribute to sustainable agricultural development in the region.